The influence of parent–child relationships on the learning adaptability of left-behind children: the mediating role of peer attachment and the moderating role of separation duration - Chen, Ning; Zhao, Keyun; Chen, I-Hua; Liu, Guanling (Frontiers in Psychology, 2023)
Studies have revealed the influence of parent–child relationships on the learning adaptability of left-behind children. However, the researchers have not explored the mechanisms underlying the parent–child relationships of left-behind children. The purpose of this study was not only to examine the mediating role of peer attachment in the relationship between parent–child relationships and learning adaptability but also to explore the moderating variable of separation duration in the relationship between parent–child relationships and peer attachment. The study examined 1,555 left-behind children and found that, after controlling for gender and grade, parent–child relationships positively predicted learning adaptability; peer attachment mediated the relationship between parent–child relationships and learning adaptability, and separation duration moderated the effect of parent–child relationships on peer attachment. The study reveals the importance of parent–child relationships and peer attachment in the growth and development of left-behind children, which is important for the improvement of left-behind children’s learning adaptability.